المنهجية الاقتصادية لابن خلدون (دراسة نقد و تحليل علي ضوء القرآن الکريم و نهج‌البلاغة) - الدکتور حسن جلالی / جامعة أمیر المؤمنین(ع) – اهواز /الدکتور سید محمد هاشم پور مولا- کلیة الإلهيات / جامعة شیراز ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
The author aim to investigate Ibn Khuldoon`s methodology in analyzing the economic affairs in the Islamic societies and then criticising  it based on Quran and Nahj-ul-balagha which contains Ali Ibn Abi Talib`s words. This research is distinguished by criticising and analyzing Ibn Khuldoon`s methodology by showing the details of his opinions and thoughts in the field of economy.The hypothis of this research is that Ibn Khuldoon was influenced a lot by the positivism and experiential sience in analyzing the economic affairs and theorizing on them that opposes what is understood from Quran and Nahj-ul-balagha.The result of this research improves that Ibn Khuldoon`s methodology in the economic is a positivist – experiential methodology in which the Islamic principles are neglected. Thus, he tried to generalize the results to the similar subjects although he has stipulated that some results he has deduced are relative. Of cours, that Ibn Khuldoon`s methodology opposes what Islam has accepted to believe the variety and multiplicity of the methodology.